Empowering Millennial Muslim Families through Artifical Intelligence in Qur’anic Learning : Opportunities and Ethical Challenges in Indonesia - Misbahati Putri, Bella; Salim, Hakimuddin; Inayati, Nurul Latifatul (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to analyze the experiences and perceptions of millennial Muslim families in Artificial Intelligence-based applications used for Qur'anic learning and identify the challenges faced by millennial Muslim families. Secondary data research methods will be used in the research. To conduct this study, researchers need to read relevant literature from secondary sources that include journal articles and books on: AI technology in Islamic education; the implementation of AI technology in educational research; development of AI applications in learning the Qur'an. However, despite the advantages, the results of the study show that the application of AI in learning the Qur'an has various challenges. Primarily, they include a limited understanding of accent and voice pronunciation, a lack of social interaction that affects the spiritual aspects of the learning process, and ethical issues and user data privacy. Later, technological resistance changed among Muslim communities; This is also another factor that affects the acceptance of applications. In general, the study concludes that while AI is a useful tool in learning the Qur'an, a combined learning approach requires AI, as well as other interests in learning, bringing recommendations to improve effectiveness and provide a cohesive experience. App developers are advised to improve speech recognition technology, provide more varied datasets, incorporate automated tajweed scoring systems, and pay attention to data security and ethical considerations. It is recommended that more research be done to measure the efficacy of these apps through direct user experiments.